Oxidative stability of Echium plantagineum oil - Roschel, Gabriela Grassmann (2020)
The evidences about the cardioprotective effects of omega-3 fatty acids (n-3 FA), especially EPA (eicosapentaenoic acid) and DHA (docosahexaenoic acid), have increased the consumption of these fatty acids. Echium plantagineum is a plant from Boragenacea family, known as potential source of non-marine omega-3 fatty acids (n-3 FA). Echium seeds presents 12-16% of stearidonic acid (SDA), that can be converted to EPA and DHA at a more elevated rate than the conversion obtained from α-linolenic acid (ALA), present in several other vegetable oils. However, echium oil is highly susceptible to oxidation because it has a high proportion of polyunsaturated fatty acids. Thus, the objective of this study was to combine three natural strategies to inhibit the oxidative damage in echium oil. In the first step, a mixture containing hydrophilic (HM: synaptic + ascorbic + citric acids) or lipophilic (LM: α-tocopherol + ascorbyl palmitate + citric acid) antioxidants was applied in the flaxseed oil, kept at 40oC/ 15 days. The oxidative markers were compared with the oil added of TBHQ (120 ppm) and EDTA (75 ppm), both artificial compounds. The results showed that LM and HM had an oxidative protection similar to the artificial antioxidants and that, HM promoted a better protection than LM. Based on this result, HM was selected as a strategy to be applied in the next step. In the second part of this study, Echium oil was obtained by two process: continuous screew pressing (PRESS) and extraction using hexane (SOLV). Both samples were added of HM combined with a high oleic sunflower oil and kept at different temperatures during storage. Two conditions were analyzed: 6 months into sealed flasks and 30 days into opened flasks. Oxidation reaction was followed by measuring the concentration of hydroperoxide, malondialdehyde, tocopherol and volatile compounds. In general, results showed that temperature reduction was enough to keep the oils stability during storage. Thus, the focus of the strategy\'s combination was directed toward samples after exposition to oxygen. In this context, better results were obtained by blending 20% of high oleic sunflower oil and the hydrophilic antioxidant mixture (500 ppm of synaptic acid, 250 ppm of ascorbic acid and 150 ppm of citric acid). In this condition it was observed 37-41% reduction in the hydroperoxide values and 40-75% in the malondialdehyde concentration in the samples prepared according to the optimized condition, when compared with the standard conditions by which the oil is currently extracted and processed.